59-01: SafeR is associated with a risk reduction of first-onset AF in patients with atrio-ventricular blocks: results from the ANSWER study. (10th June 2016) - Fauchier, Laurent; Boveda, Serge; Moreno, Javier; Defaye, Pascal; Stockburger, Martin
Abstract: Atrial fibrillation (AF) is a frequent incident comorbidity in the pacemaker patient population and has been associated with higher risk of heart failure, stroke and death. The SafeR pacing mode is designed to manage first-, second- and third-degree atrio-ventricular blocks (AVB); and its effectiveness has been demonstrated in the randomized, multicenter ANSWER trial on both patients implanted for sinus node disease or AVB. We sought to investigate specifically for AVB patients the possible benefit associated with SafeR for first onset of AF. Methods: The first onset of AF was ascertained from the pacemaker memory. Predictors of AF were identified using a Cox proportional-hazards model in patients implanted for AVB (n = 186, 70.3 ± 12.2 years, 65.1% males), without any history of atrial arrhythmias either prior to enrollment or during the 1st month after randomization. Results were adjusted on age, gender, coronary disease, cardiomyopathy, valvular disease, LVEF, HF history, diabetes. Results: Over 3 years, 96 (51.3%) patients experienced first-onset AF. Of this group, 42 (47.2%) were programmed in SafeR and 54 (55.7%) in DDD mode. SafeR was associated with a 35% risk reduction in the first onset of AF (adjusted HR = 0.65, 95% CI: [0.43-0.98], p = 0.038), as compared to DDD (Figure). No other parameter studied was predictive of AF incidence. Conclusion: The SafeR mode is associated with a significantly reduced risk of first-onset AF as compared with DDD in AVB patients.